1998
DOI: 10.1002/(sici)1098-2744(199812)23:4<195::aid-mc1>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Identical variantTSG101 transcripts in soft tissue sarcomas and various non-neoplastic tissues

Abstract: Inactivation of the TSG101 gene was recently shown to induce malignant transformation of NIH/3T3 fibroblasts. Abnormal TSG101 transcription profiles were observed in various human cancers, and large intragenic deletions of the TSG101 gene were reported for a series of human breast cancer specimens, pointing to a potential tumor-suppressive activity of TSG101. However, subsequent more detailed studies on a large panel of breast carcinoma samples did not confirm the tumor-associated genomic deletions. Here we an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…These shorter RT ± PCR fragments varied in size and abundance compared to the full-length product. Note, however, that the abnormal fragment was in much lower abundance than the full-length one, as previously shown (Chang et al, 1999;Gayther et al, 1997;Lee and Feinberg, 1997;Li et al, 1997;Sun et al, 1997;Willeke et al, 1998). The speci®city of the shorter PCR fragments was veri®ed by Southern blot hybridization using a cDNA fragment internal to the primers as a probe (Figure 1b).…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…These shorter RT ± PCR fragments varied in size and abundance compared to the full-length product. Note, however, that the abnormal fragment was in much lower abundance than the full-length one, as previously shown (Chang et al, 1999;Gayther et al, 1997;Lee and Feinberg, 1997;Li et al, 1997;Sun et al, 1997;Willeke et al, 1998). The speci®city of the shorter PCR fragments was veri®ed by Southern blot hybridization using a cDNA fragment internal to the primers as a probe (Figure 1b).…”
Section: Resultssupporting
confidence: 57%
“…The speci®city of the shorter PCR fragments was veri®ed by Southern blot hybridization using a cDNA fragment internal to the primers as a probe (Figure 1b). Sequence analysis showed that the abnormal fragment in Figure 1a, lane 3 (550 bp, deletion nt 133 ± 730) was previously described in other cancer samples (Chang et al, 1999;Gayther et al, 1997;Lee and Feinberg, 1997;Sun et al, 1997;Willeke et al, 1998). Southern blot analysis of the ®rst round PCR products allowed the detection of few truncated forms, demonstrating that truncation is not an artifact of the nested PCR procedure (not shown).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Aberrant splicing and production of TSG101 transcript variations have been detected in multiple types of human cancer, including carcinomas of the liver, lung, breast, cervix, and ovary [46] - [50] as well as in soft tissue sarcomas [51] , and leukemias [52] . It has been suggested that such aberrant transcripts are experimental artifacts of PCR analysis [53] ; however, it also has been reported that induction of the tumor suppressor gene p53 prevents the accumulation of variant transcripts [54] .…”
Section: Discussionmentioning
confidence: 99%
“…The human homologue TSG101 has been isolated and mapped to chromosome 11p, bands 15.1-15.2 (Li et al, 1997), a region known to exhibit a high incidence of loss of heterozygosity in a variety of human malignancies (Ali et al, 1987;Baffa et al, 1996;Byrne et al, 1993;Lothe et al, 1993;Ludwig et al, 1991;Reeve et al, 1989;Shaw and Knowles, 1995;Weitzel et al, 1994), suggesting that TSG101 might be a tumor suppressor. Although no genomic deletion has been identified, aberrant transcripts can be found in various tumors and their matched normal tissues (Carney et al, 1998;Chang et al, 1999;Lee and Feinberg, 1997;Lin et al, 1998a,b;Wang et al, 2000;Willeke et al, 1998), including thyroid tumors (McIver et al, 2000). Abnormally spliced transcripts of TSG101 have been found to very closely correlate with tumor grade and p53 mutation in breast cancer samples.…”
Section: Introductionmentioning
confidence: 99%